Reputation-based Decentralized Autonomous Organization for the non-profit sector: Leveraging blockchain to enhance good governance - Saito, Yoshiro; Rose, John A. (Frontiers in Blockchain, 2023)
The Decentralized Autonomous Organization (DAO), a group organized by governance rules programmed on a blockchain, has recently been attracting attention as a novel organizational form. The effectiveness of a DAO's decentralized governance mechanism and transparency, as secured by its code, has generally been discussed in contrast with traditional stock companies. However, the potential of a DAO for nonprofits, which provide goods and services that profit-seeking organizations do not offer, has been less discussed. This paper presents a proof-of-concept implementation to demonstrate the advantages of utilizing a DAO governance framework for nonprofits. To this end, this study developed a DAO governance framework incorporating a reputation-based decision-making system, a peer evaluation system, and a transparent, real-time accounting system for the Ethereum blockchain. Most current decentralized governance systems rely heavily on token-based voting using governance tokens with stock-like features. However, there is a need for a voting mechanism beyond token-based voting for nonprofits, which do not have owners. Therefore, the developed application applies an existing reputation-based voting mechanism and integrates additional features, such as a membership system with mutual evaluation and a reputation NFT to visualize contributions. Several exemplar demonstrations were conducted to evaluate its key functionalities. This application enabled discussions across the boundary between technology and society in terms of the key aspects of nonprofits: (i) transparency of finance and governance, (ii) participatory governance by diverse stakeholders, and (iii) equity and inclusiveness of the consensus mechanism. The results indicated that blockchain technology compensates for a nonprofit's vulnerabilities, and illustrated that the proposed reputation-based governance mechanisms are well-motivated. However, the results also revealed that blockchain-based governance involves as many potential risks and limitations as it brings benefits. Lastly, by providing several possible solutions to these constraints as well as recommendations for future research, this paper contributes to the sustainable development of nonprofits as one of the foundations of democratic governance.